ANALISIS KELINCAHAN DAN KOORDINASI TERHADAP KEMAMPUAN MENGGIRING BOLA PADA MURID SDN 44 PALANGKA - Ahmad Adil; Andi Ihsan; Abdul Rahman; Muh. Adnan Hudain; Fahrizal Fahrizal (Program Studi Ilmu Keolahragaan, 2023)
This study aims to obtain answers to the problems: (1) Is there a relationship between agility and the ability to dribble in a soccer game (2) Is there a relationship between coordination and the ability to dribble in a soccer game (3) Is there a joint relationship between agility and coordination on the ability to dribble in soccer games. This research is descriptive in nature towards two independent variables and one dependent variable. the sample is students of SDN 44 Palangka with a total sample of 25 people. Data analysis technique using correlation (R-test) Based on the results of data analysis can be interpreted as follows: (1). There is a relationship between agility and the ability to dribble in soccer games, where the value of r = 0.780 (P < 0.05). with a linkage or contribution of 60.9%. (2). There is a relationship between coordination and the ability to dribble in soccer games, where the value of r = 0.666 (P <0.05). with a link or contribution of 44.3%. (3). There is a relationship between agility and coordination on the ability to dribble in soccer games, where the value of R = 0.7791 (P <0.05). with a linkage or contribution of 62.6%.